Poorer Financial and Health Literacy Among Community-Dwelling Older Adults With Mild Cognitive Impairment - Han, S. Duke (J Aging Health, 2015)
OBJECTIVE: Literacy is an important determinant of financial and health outcomes in old age, and cognitive decline has been linked with lower literacy. We tested the hypothesis that mild cognitive impairment (MCI) is associated with poorer financial and health literacy. METHOD: Participants (n = 730) from the Rush Memory and Aging Project were given a clinical evaluation and an assessment of total, financial, and health literacy. Regression was used to examine whether MCI was associated with lower literacy. In secondary analyses, we investigated the association of particular cognitive systems with literacy. RESULTS: MCI was associated with lower total, financial, and health literacy. An interaction was observed such that higher education reduced the effect of MCI on total and financial literacy. Multiple cognitive systems were associated with literacy in participants with MCI, and semantic memory accounted for the most variance. DISCUSSION: Persons with MCI exhibit poorer financial and health literacy, and education mitigates this effect.